Enhancing Statistical Physics Learning: Rhetoric and Emotion in Moodle for Physics Education - Erlangga, S. Y.; Winingsih, P. H.; Yektyastuti, R.; Poort, E. A.; Amrurrahim, A. N. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2023)
The Learning Management System in science education has become crucial in modern educational settings. However, there is a lack of comprehensive resources to guide the implementation of hedonic and pragmatic qualities in UX. This study aims to identify emotional design factors and adopt an innovative perspective with a rhetorical approach to enhance the user experience. This study adopts the Design-Based Research methodology using the UEQ questionnaire with 26 items, involving a total population of 122 students. Conducting research through a User Experience Questionnaire, rhetorical evaluation, and open-ended questions in three control groups, the physics learning experience through Moodle at the Sarjanawiyata Tamansiswa University was evaluated, specifically in the Physics Education study program. The research findings demonstrate that improving UX leads to higher user satisfaction. According to the results of the UEQ analysis, it is evident that attractiveness, clarity, and efficiency are rated above average. Meanwhile, aspects of dependability, stimulation, and novelty are assessed below average criteria. The study concludes that ethos, pathos, and logos are essential in embracing the pragmatic and hedonic aspects of UX.